Jumlah kandungan elektron sewaktu gangguan ionosfera bergerak di Parit Raja, Johor - Mardina Abdullah,; Dayang Azra Awang Mat,; Ahmad Faizal Mohd Zain,; Sabirin Abdullah,; Asnawi,; Siti Sarah Nik Zulkifli, (2010)
Travelling ionospheric disturbance (TID) is a phenomenon caused by solar activity and TID strength varies by locations, especially in equatorial regions. This phenomenon affects the local total electron content (TEC), especially during the daytime. Because of this, research regarding augmenting TEC values during TID is done by comparing TEC values obtained from the IRI2001 and NeQuick models with IONEX data. By using Global Positioning System (GPS) data obtained from the Parit Raja station in the southern part of Malaysia (1º 52’ N, 103º 06’ E) as reference, research was conducted during geomagnetic quiet day as well as on the disturbed day. The occurrence of TID can clearly be seen when using the real TEC data from IONEX and WARAS. Result obtained from Parit Raja station shows a much more significant effect of TID occurrence on TEC than what was shown by IONEX data. However, the TEC values obtained from the IRI2001 and NeQuick models were influenced by the number of sunspots and were only applicable in geomagnetic quiet days. In order to obtain more accurate TEC values, it is necessary to ensure that TID condition is included in the IRI2001 and NeQuick models